Fluorescence Diagnosis in Neurooncology: Retrospective Analysis of 653 Cases - Goryaynov, Sergey A.; Okhlopkov, Vladimir A.; Golbin, Denis A.; Chernyshov, Konstantin A.; Svistov, Dmitrij V.; Martynov, Boris V.; Kim, Alexandr V.; Byvaltsev, Vadim A.; Pavlova, Galina V.; Batalov, Artem; Konovalov, Nikolay A.; Zelenkov, Petr V.; et al. (Frontiers in Oncology, 2019)
Abstract The objective of this study is to analyze fluorescence sensitivity in diagnosis of brain and spinal cord tumors. Material and methods. The authors conducted a multicenter retrospective analysis of 653 cases in 641 patients: 553 of them had brain tumors, and 88 spinal cord tumors. Brain tumor resection was performed in 523 patients, of whom 484 were adults and 39 children. The analyzed series was presented by 320 gliomas, 101 meningiomas and 72 metastases. Stereotactic biopsy was performed in 20 patients and endoscopic surgery in 10 patients. In all cases 20 mg/kg of 5–Aminolaevulinic acid was administered orally 2-h before surgery. All surgical interventions were performed with a microscope BLUE 400 to visualize fluorescence, while endoscopic surgery – with an endoscope equipped with a fluorescent module. Fluorescence spectroscopy was conducted in 20 cases of stereotactic biopsies and in 88 cases of spinal cord tumors. Results. Among adult brain tumors operated by microsurgical techniques, meningiomas showed the highest 5-ALA fluorescence sensitivity 94% (n=95/101), brain metastases 84,7% (n=61/72), low-grade gliomas 46,4% (n=26/56), and high-grade gliomas 90,2% (n=238/264). In children the highest 5-ALA visible fluorescence was observed in anaplastic astrocytomas 100% (n=4/4) and in anaplastic ependymomas 100% (n=4/4); in low-grade gliomas it made up 31,8% (n=7/22). As for the spinal cord tumors in adults, the highest sensitivity was demonstrated by glioblastomas 100% (n=4/4) and by meningiomas 100% (n=4/4); Fluorescence was not found in gemangioblastomas (n=0/6) and neurinomas (n=0/4). Fluorescence intensity reached 60% (n=6/10) in endoscopic surgery and 90% (n=18/20) in stereotactic biopsy. Conclusion. Based on a large series of our patients with a great variety of histological tumor types, it was concluded, that a neurosurgeon can predict fluorescence sensitivity before surgery.